An edge inspired image watermarking approach using compass edge detector and LSB in cybersecurity - Bin Faheem, Zaid; Hanif, Danial; Arslan, Farrukh; Ali, Mubashir; Hussain, Aamir; Ali, Jehad; Baz, Abdullah (Computers and Electrical Engineering, 2023)
In the contemporary era, data holds a vital significance, and ensuring the security of data stands as an exceptionally challenging endeavor. Both industry and academia dedicate substantial efforts to mitigate security breaches. Given the evolving nature of modern cyber threats, there arises a compelling necessity for robust cybersecurity measures concerning digital content. We propose the merits of digital watermarking within the realm of cybersecurity for digital content. Researchers within the watermarking domain are diligently striving to offer the utmost security services. Unfortunately, achieving both robustness and security concurrently within these techniques has proven to be a formidable task. Hence, we delve into a novel approach for image watermarking, which draws inspiration from gradient-based methodologies. This scheme hinges upon compass edge detection, the least significant bit mechanism, and the utilization of chaotic encryption for watermark embedding. The effectiveness and performance are rigorously evaluated against a spectrum of geometrical and image-processing attacks.
Keywords: Chaotic encryptions; Cyber security; Cyber threats; Digital contents; Edge detectors; Gradient based; Least significant bits; Security breaches; Security services; Substitution box; Cybersecurity; Image watermarking; Least significant bit; Substitution box